The growth of the urban area of São Carlos/SP between the 2010 and 2015: The advancement of environmental degradation - Stanganini, Fábio Noel; de Lollo, José Augusto [UNESP] (FapUNIFESP (SciELO), 2018)
The objective of this study was to analyze the progress of environmental degradation in the municipality of São Carlos, Sao Paulo state, as a result of the urban area growth process between 2010 and 2015. The following aspects were addressed: the anthropogenic activities that caused environmental degradation and the urban area growth and its relation to environmental impacts. To this end, spatial analysis tools such as Geographic Information Systems (GIS), remote sensing, and digital cartography were used, enabling temporal analysis through detailed observation and monitoring of the urban area current situation. An alarming situation of uncontrolled growth was detected, which is a result of a disperse and unregulated process on the soil, highlighting the need for better control of this process and, mainly, for implementation of urban management tools. There are indications that the environmental problems will continue to evolve as a result this urban area growth process, which indicates a potential for degradation of areas not yet affected.
O crescimento da área urbana da cidade de São Carlos/SP entre os anos de 2010 e 2015: O Avanço da degradação ambiental
Keywords: Environmental degradation; Environmental impacts; Geoprocessing; Urban growth; Urban planning